TAFSIR AL-AZHAR: SUATU TINJAUAN BIOGRAFIS DAN METODOLOGIS - Malkan, Malkan (Hunafa: Jurnal Studia Islamika, 2009)
This article deals with TafsÃ®r al-AzhÃ¢r from biographical and methodological perspectives employing historical method. Hamka started writing this TafsÃ®r al-AzhÃ¢rÂ  in 1959 than convoyed it as a down lecture in the Mosque of al-AzhÃ¢r. He completed the writing of this book of al-tafsÃ®r when he wasÂ  being jailed. This book of al-tafsÃ®r consists of thirty chaptersl. After analyzing the contents of the book of al-tafsÃ®r, the writer found that Hamka employed rational method with literature and social patterns based on the school of Islamic orthodoxy and Islamic free act.Kata Kunci: Â Â  Hamka, TafsÃ®r al- AzhÃ¢r, tafsir bi al-matsur, Â tafsir bi al-ray, metode tahlilÃ®,Â  corak penafsiran adabÃ®, corak penafisran ijtimÃ¢âÃ®